Evaluation of second-line apatinib plus irinotecan as a treatment for advanced gastric adenocarcinoma or gastroesophageal conjunction adenocarcinoma: a prospective, multicenter phase II trial - Qu, Jinglei; He, Xin; Luo, Ying; Yu, Ping; Chen, Ying; Liu, Jing; Wang, Xin; Wang, Chang; Liang, Tingting; Bai, Yuxian; Han, Yu; Man, Li; et al. (Frontiers in Oncology, 2023)
Objective: Apatinib and irinotecan are used as systematic therapies for advanced gastric adenocarcinoma (GAC) and gastroesophageal junction adenocarcinoma (GEJA), while the evidence for their combination as second-line therapy in these patients is limited. This study aimed to evaluate the efficacy and safety of second-line apatinib plus irinotecan for the treatment of GAC and GEJA. Methods: In this prospective, multicenter phase II clinical study, 28 patients with advanced GAC or GEJA who received second-line apatinib plus irinotecan were recruited. Results: In total, 1 (3.6%) patient achieved complete response, 7 (25.0%) patients achieved partial response, 13 (46.4%) patients had stable disease, and 4 (14.3%) patients showed progressive disease, while clinical response was not evaluable or not assessed in 3 (10.7%) patients. The objective response rate and disease control rate were 28.6% and 75.0%, respectively. Meanwhile, the median (95% confidence interval (CI)) progression-free survival (PFS) was 4.5 (3.9-5.1) months, and the median (95% CI) overall survival (OS) was 11.3 (7.4-15.1) months. By multivariate Cox regression analysis, male sex, liver metastasis, and peritoneal metastasis were independently associated with worse PFS or OS, while treatment duration ≥5 months was independently associated with better OS. In terms of the safety profile, 89.3% of patients experienced treatment-emergent adverse events of any grade, among which 82.1% of patients had grade 1-2 adverse events and 64.3% of patients had grade 3-4 adverse events. Conclusion: Apatinib plus irinotecan as second-line therapy achieves a good treatment response and satisfactory survival with tolerable safety in patients with advanced GAC or GEJA.